2022
DOI: 10.26434/chemrxiv-2022-f1hv5-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fully degradable polymer networks from conventional radical polymerization of vinyl monomers enabled by thionolactone addition

Abstract: We report the preparation of degradable polymer networks by conventional free radical copolymerization of n-butyl acrylate with a crosslinker (1 mol%) and dibenzo[c,e]oxepane-5-thione (DOT) as a strand-cleaving comonomer. Addition of only 4 mol% of DOT imparts the synthesized networks with full degradability by aminolysis, whereas gels with less DOT (2-3 mol%) cannot be degraded, in excellent agreement with the recently proposed reverse gel-point model. Importantly, even though DOT significantly slows down the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Additionally, the very recent work by Johnson et al showed recyclability of DOT-containing polystyrene and could potentially be extended to crosslinked systems offering a way to circular vinyl thermosets. We therefore expect increased interest in thionolactones for the preparation of degradable networks …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the very recent work by Johnson et al showed recyclability of DOT-containing polystyrene and could potentially be extended to crosslinked systems offering a way to circular vinyl thermosets. We therefore expect increased interest in thionolactones for the preparation of degradable networks …”
Section: Discussionmentioning
confidence: 99%